Implementation of Mesi Quper (Media Edukasi Quizizz Kombinasi Peardeck) for Optimizing Differentiated Learning in Class V of SDN 1 Kalitapen - Neysa Dika Putri; Wakhudin Wakhudin (UM Purwokerto Press, 2025)
The lack of educational media usage in learning has become a major issue in achieving students literacy competencies. This impacts to suboptimal differentiated learning implementation. This paper aims to analyze the impact of applying Quizizz combined with Peardeck to improve literacy learning and evaluation results of students in class V of SDN 1 Kalitapen. This research employs a qualitative descriptive approach by collecting data through observation, interviews, implementation, and documentation. Data analysis techniques involve field data collection, data reduction, data presentation, application and development of media, as well as conclusions and verification. The results of this good practice indicate an improvement in literacy skills through the use of Quizizz educational media combined with Peardeck, with an increase of 4.34% from the previous year, categorized as good (80% of students achieving minimum competency), so that the school ranks in the top tier (1-20%) in the district/city nationally.